Nanoencapsulation and Characterization of Zidovudine on Poly(L-lactide) and Poly(L-lactide)-Poly(ethylene glycol)-Blend Nanoparticles - Mainardes, Rubiana Mara; Gremião, Maria Palmira Daflon [UNESP] (Amer Scientific Publishers, 2012)
In this work, the antiretroviral zidovudine was encapsulated on biodegradable poly(L-lactide) (PLA) or poly(L-lactide)-poly(ethylene glycol) (PLA-PEG)-blend nanoparticles by the double-emulsion solvent-evaporation method. The PLA-PEG blend was obtained by the physical mixture of the isolated polymers in organic solvent, whose PEG content ranges from 5 to 50 g in the blends. The physicochemical characteristics of the nanoparticles were evaluated applying particle-size and zeta-potential analyses, scanning electron microscopy, differential scanning calorimetry and Fourier-transform infrared spectroscopy. The release rate of zidovudine from the nanoparticles was investigated as well. The drug encapsulation efficiencies were around 50%, and the mean diameters of the nanoparticles were less than 400 nm. The PEG presence influenced all of the analyzed physicochemical parameters. The amount of drug released increases with the PEG presence in the blend. Therefore, the investigated nanoparticles are very promising carriers for zidovudine.
Keywords: Nanoparticles; Biodegradable Polymers; PLA; PLA-PEG; Drug Delivery; Zidovudine